A Review of Medicinal Plant Patents - Pennyroyal, Greg; Dhondup, Lobsang; Husted, Cynthia (Recent Patents on Biomedical Engineering (Discontinued), 2011)
Medicinal plant formulations have been used in traditional medicines for thousands of years. Plant-based medicine is still a major source of new drug leads and herbal treatments are highly lucrative in the international marketplace. The intellectual property issues for medicinal plant formulas are complicated for numerous reasons. Many of the patents are attempting to emulate the pharmaceutical model of composition patents that as we will discuss, is usually not an appropriate approach for medicinal plants. This paper does not seek to be an exhaustive review but rather provide an overview of the many aspects of medicinal plant patents, a topic of considerable future growth. Our experience has been that the merging of modern and traditional knowledge leads to unexpected correlations, elucidations and insights with tremendous potential for patentable discovery. A continuation of the dialogue on indigenous intellectual property rights will benefit from the inclusion of an increased diversity of voices that have the ability to recognize the mutual and often complementary abilities of traditional and modern sciences. The question is not how to simplify the complexity but rather how to embrace the complexity from the traditional medicine worldview with the tools of science.
Keywords: PUBLIC HEALTH